Reliability Estimation when Failure Intensity Depends on Calendar Time - Kruopis, J.; Levulienė, R. (Elektronika ir Elektrotechnika, 2009)
In many practical situations the failure rate of products depends not only on their age but also on the date (calendar time). For example, at different dates the characteristics of spares of products, the technologic process, exploitation conditions may be different. Similar situations may be observed for other practical applications. For example, insurance companies: the mortality of individuals depends not only on their age but also on the calendar time (flu epidemic, accident rate and etc). The problem of failure rate estimation was investigated when the failure rate of products depends not only on their age but also on the date (calendar time) and statistical data are grouped into some intervals of product age and calendar time. The mathematical model was proposed. The parameter estimators were obtained. The test of model consistency was constructed. Ill. 3, bibl. 3 (in English; summaries in English, Russian and Lithuanian).